Netcentric system of systems engineering with DEVS unified process - Mittal, Saurabh; Risco-Martin, Jose Luis.; Cetinkaya, Deniz; Verbraeck, Alexander; Seck, Mamadou D. (Boca Raton : Taylor & Francis, 2013)
"Addressing the new challenges that engineers face, this book presents fundamental concepts to help tackle the integration of modeling and simulation with command, and control systems of systems through the use of concepts and standards for interoperability and testing based on the Discrete Event Systems Specification Unified Process. The text presents state-of-the-art modeling and simulation methodologies in system-of-systems engineering, focusing on the development of modeling and simulation based net-centric systems of systems. The author aims to provide a foundation for net-centric systems software engineering. This seminal text is based on the Department of Defense Architecture Framework"--
section 1. The basics -- section 2. Modeling and simulation-based systems engineering -- section 3. Netcentric system of systems -- section 4. Case studies -- section 5. Next steps.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Systems engineering -- Data processing; Internetworking (Telecommunication); Discrete-time systems -- Computer simulation; Electronic books